1975
DOI: 10.1002/ajpa.1330430321
|View full text |Cite
|
Sign up to set email alerts
|

Role of light in human skin color variation

Abstract: The major source of color in human skin derives from the presence within the epidermis of specialized melanin-bearing organelles, the melanosomes. Tanning of human skin on exposure to ultraviolet light results from increased amounts of melanin within the epidermis. Melanosomes synthesized by melanocytes are acquired by keratinocytes and transported within them to the epidermal surface. In some cases, the melanosomes are catobolized en route. New information indicates that the multicellular epidermal melanin un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
6

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 41 publications
0
38
0
6
Order By: Relevance
“…This would suggest that white skin carries a selective advantage in northern latitudes. Quevedo et al (1975) have reviewed the theories which have been advanced to explain this, and concluded that the most attractive was that concerning the synthesis of vitamin D. This vitamin is rare in most foods but can be synthesized in the skin under the action of sunlight. In northerly latitudes a greater proportion of the available sunlight would need to be absorbed to produce sufficient vitamin D. There must however be a compromise between a skin which is light enough to absorb enough UV and one which is pigmented enough to protect against sunburn, solar degeneration and skin cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would suggest that white skin carries a selective advantage in northern latitudes. Quevedo et al (1975) have reviewed the theories which have been advanced to explain this, and concluded that the most attractive was that concerning the synthesis of vitamin D. This vitamin is rare in most foods but can be synthesized in the skin under the action of sunlight. In northerly latitudes a greater proportion of the available sunlight would need to be absorbed to produce sufficient vitamin D. There must however be a compromise between a skin which is light enough to absorb enough UV and one which is pigmented enough to protect against sunburn, solar degeneration and skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence among darkskinned races is commonly low (Oettle, 1]966;Camain et al, 1972) and a clear relationship between the density of skin pigmentation and the incidence of melanoma on the exposed body sites has been demonstrated (Crombie, 1979). Melanin pigmentation is thought to afford protection by absorbing the UV (Quevedo et al, 1975) so that the degree of protection would be expected to depend on the concentration of pigment.…”
mentioning
confidence: 99%
“…1b). The latter class is particularly interesting from the perspective of human genetics, as normal variation in human skin color is mediated by changes in melanocyte activity rather than melanocyte number (Toda et al 1972;Quevedo et al 1975;Quevedo and Holstein 1998). Beside rare mutations that cause oculocutaneous albinism, the only human skin color gene identified to date is the melanocortin 1 receptor, in which loss-of-function variants cause fair skin and red hair (Rees et al 1999;Sturm et al 2001).…”
Section: Development and Pathophysiology Of Dark Skinmentioning
confidence: 99%
“…These included: children's age, sex (Hagenau et al 2009;Lagunova et al 2009;Rockell et al 2005), skin pigmentation (Maguire et al 2013), BMI z-score (zBMI), daily vitamin D supplementation, daily volume of milk consumed, date of blood collection, non-cow's milk consumption, and median neighbourhood family income (Statistics Canada 2014). The Fitzpatrick scale was used to assess skin pigmentation, an acceptable method for skin pigmentation quantification used in dermatological research (Fitzpatrick 1988;Quevedo et al 1975).…”
Section: Subjects and Designmentioning
confidence: 99%